2017
DOI: 10.1038/s41598-017-08349-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of high-expression of miR-17-92 cluster in various tumors: evidence from a meta-analysis

Abstract: The prognostic value of miR-17-92 cluster high-expression in various tumors remains controversial. Therefore, we conducted this meta-analysis by searching literatures in PubMed, Embase, Cochrane Library, China Biology Medicine disc, China National Knowledge Infrastructure to identify eligible studies. Eventually, we analyzed 36 articles that examined 17 tumor types from 4965 patients. Consequently, high-expression of miR-17-92 cluster in various tumors was associated with unfavorable overall survival in both u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…In addition, by conducting survival analysis using the TCGA database, our study is the first to reveal that miR-18a expression is negatively correlated with patient survival outcome in MM, which is consistent with our previous data in MM showing a positive correlation between PIAS3 protein expression and patient survival outcome (Dabir et al, 2014). Much of the attention focused on miR-18a stems from it being a member of the miR-17-92 cluster, which was one of the first tumorigenic clusters identified (Zhang et al, 2017b). A previous study in MM has shown that the miR-17-92 cluster is globally upregulated in MM cells compared to normal tissue (Balatti et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, by conducting survival analysis using the TCGA database, our study is the first to reveal that miR-18a expression is negatively correlated with patient survival outcome in MM, which is consistent with our previous data in MM showing a positive correlation between PIAS3 protein expression and patient survival outcome (Dabir et al, 2014). Much of the attention focused on miR-18a stems from it being a member of the miR-17-92 cluster, which was one of the first tumorigenic clusters identified (Zhang et al, 2017b). A previous study in MM has shown that the miR-17-92 cluster is globally upregulated in MM cells compared to normal tissue (Balatti et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Much of the attention focused on miR‐18a stems from it being a member of the miR‐17‐92 cluster, which was one of the first tumorigenic clusters identified (Zhang et al ., 2017b). A previous study in MM has shown that the miR‐17‐92 cluster is globally upregulated in MM cells compared to normal tissue (Balatti et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the miR-17-92 family, can increase proliferation of tumor cells by affecting their cell cycle [ 11 ]. Moreover, as miR-17-92 is relatively more sensitive, specific, and accurate [based on the area under the receiver operating characteristic (ROC) curve], it could be used as a marker for tumor identification, prognosis evaluation, and recurrence monitoring [ 12 18 ]. The potential use of miR-17-92 as a marker sets a new path for the development of microRNA-derived molecular medicine for colon cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported an association between high expression levels of specific miRNAs (including miR-21, miR-1290, miR-193a, miR-17-5p, miR-92a-3p, miR-203, miR-1229, and miR-17/92 cluster) and poor prognosis of CRC patients due to metastatic disease, post-treatment relapse, and poor OS [ 48 , 49 , 82 , 83 , 84 , 85 , 86 ]. On the other hand, low levels of serum exosomal miR-4772-3p and miR-6869-5p were associated with high risk of tumor recurrence in stage II and III and poor 3-year survival in CRC patients, respectively [ 50 , 51 ].…”
Section: Clinical Utility Of Liquid Biopsies In Patients With Colomentioning
confidence: 99%